Discoveries of the Other : Alterity in the Work of Leonard Cohen, Hubert Aquin, Michael Ondaatje, and Nicole Brossard - Siemerling, Winfried, 1956- (Book collections on Project MUSE., 1994)
Siemerling concludes that the works under consideration offer heterological discoveries that maintain a productive 'negativity' (Kristeva) with respect to given knowledge and fixed articulations of self and other.